Tree diversity as affected by salinity in the Sundarban Mangrove Forests, Bangladesh - Ahmed, Ashfaque; Aziz, Abdul; Khan, AZM Nowsher Ali; Islam, Mohammad Nurul; Iqubal, Kazi Farhed; Nazma, M; Islam, Md Shafiqul (Bangladesh Journal of Botany, 2012)
A botanical expedition to the Sundarban Mangrove Forests (SMF) in March, 2010 was made to study the tree diversity and their abundance as affected by salinity gradient. In six quadrats of 25m × 25m each, distributed in all four Ranges, a total of eight tree species were recorded. A maximum number of five species occurred in relatively low saline sites. Tree zonation dynamics of the forests along salinity gradient revealed an increase in the number of Ceriops decandra (goran), a salt tolerant plant in the north-eastern parts of the SMF which was dominated by Heritiera fomes (sundri), a freshwater loving plant in 1960’s. Highest importance value index (IVI) was recorded for C. decandra, which was present in all sites, except Moroghodra, a freshwater zone in Nalianala (Khulna) Range. Comparison of the Landsat images of Nalianala and Chandpai Ranges during 1989, 2000 and 2010 revealed a decreased tendency of dominance of H. fomes in the two Ranges but increased tendency of Bruguiera sexangula (kankra), Excoecaria agallocha (gewa) and Sonneratia apetala (keora). Total tree cover in 2010 decreased by about 3% from that of 1989. The changes in the tree composition have been attributed to increased salinity. The changes in the physiography and tree composition of the two Ranges between 2000 - 1989 were considerable. Key words: Tree zonation; Salinity; Remote Sensing; GIS; Heritera fomes; Ceriops decandra DOI: http://dx.doi.org/10.3329/bjb.v40i2.9778 Bangladesh J. Bot. 40(2): 197-202 , 2011 (December)